1999
DOI: 10.1139/g99-004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of plant disease resistance gene homologues using a minimal Brassica napus L. population

Abstract: Genetic mapping of plants traditionally involves the analysis of large segregating populations. However, not all individuals in a population contribute equal amounts of genetic information. It is thus possible to achieve rough mapping using a subset of the most informative individuals in the population. We have designed a minimal Brassica napus mapping population of 23 doubled-haploid plants and have tested this method using this population in the mapping of disease resistance gene homologues in B. napus. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The RGA primers (Table 1) were designed from the conserved sequences of LRR, NBS, and PtoKin motifs from cloned resistance genes (Bent et al, 1994;Kanazin et al, 1996;Leister et al, 1996;Yu et al, 1996;Chen et al, 1998;Joyeux et al, 1999;Seah et al, 1998;Rajesh et al, 2002).…”
Section: Rga Analysismentioning
confidence: 99%
“…The RGA primers (Table 1) were designed from the conserved sequences of LRR, NBS, and PtoKin motifs from cloned resistance genes (Bent et al, 1994;Kanazin et al, 1996;Leister et al, 1996;Yu et al, 1996;Chen et al, 1998;Joyeux et al, 1999;Seah et al, 1998;Rajesh et al, 2002).…”
Section: Rga Analysismentioning
confidence: 99%
“…Furthermore, using the few conserved motifs to construct degenerate PCR primers, it has been possible to clone R-gene analogs (RGAs) from many plant species, e.g. rice and barley (Leister et al, 1996), potato (Lawrence et al, 1995), tomato (Pan et al, 2000), pepper (Parker et al, 1997), soybean (Joyeuk et al, 1999;Witham et al, 1994), common bean (Leister et al, 1998;Pitrat & Lecoq, 1980), Arabidopsis (Song et al, 1995), lettuce (Saitou & Nei, 1987), Brassica (Li et al, 1999), pea (Takada, 1979), and melon (Brotman et al, 1998, Garcia-Mas et al, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence similarity between R genes, a method using degenerate primers to target the conserved motifs has been successfully employed to isolate resistance gene analogs (RGAs) from potato (Lawrence et al, 1995), soybean (Joyeuk et al, 1999;Witham et al, 1994), rice (Leister et al, 1996), Arabidopsis spp. (Aatrs et al, 1998), lettuce (Saitou & Nei, 1987), common bean (Geffroy et al, 1999;Leister et al, 1998;Pitrat & Lecoq, 1980), melon (Brotman et al, 1998), and other monocotyledonous and dicotyledonous.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of conserved domains in resistance genes gave an opportunity to clone numerous additional resistance genes from diverse species by polymerase chain reaction (PCR) with degenerate oligo-nucleotide primers to the conserved motifs (Joyeux et al, 1999;Deng et al, 2000;Donald et al, 2002;Lacock et al, 2003;Totad et al, 2005). Aarts et al (1998) reported that 1 to 2% of the total coding capacity of the Arabidopsis genome is contributed by the NBS-LRR sequences, and genetic mapping studies of resistance gene analogues (RGAs) provided evidence that they co-segregated with resistance markers.…”
Section: Introductionmentioning
confidence: 99%